Pengembangan Kapasitas Organisasi Pada Pendidikan Tinggi Teknologi Pulp dan Kertas Universitas Riau - Shafira Amalia Ramadhani; Harapan Tua Ricky Fredy Simanjuntak; Dadang Mashur (UIR Press, 2022)
The puprose of this research is to find out and analyze about Organizational Capacity Development in Pulp and Paper Technology Vocational Education University Of Riau as well as other factors that influence Organizational Capacity Development in Pulp and Paper Technology Vocational Education University Of Riau. This research uses descriptive qualitative method. The results of this s tudy indicate that, the capacity development of PSD3-TPK is considered good, because seen from the efforts at the individual level, organizational level, and system level made to maximize the organization.this is also evidenced by the absorption of all 43 PSD3-TPK alumni in the pulp and paper industry. Another support factor identified is the shared commitment, institutional reform, and recognition of strengths and weakness